Pro-Resolving Ligands Orchestrate Phagocytosis - Decker, Christa; Sadhu, Sudeshna; Fredman, Gabrielle (Frontiers in Immunology, 2021)
The resolution of inflammation is a tissue protective program that is governed by several factors including specialized pro-resolving mediators (SPMs), proteins, gasses and nucleotides. Pro-resolving mediators activate counterregulatory programs to quell inflammation and promote tissue repair in a manner that does not compromise host defense. Phagocytes like neutrophils and macrophages play key roles in the resolution of inflammation because of their ability to remove debris, microbes and dead cells through processes including phagocytosis and efferocytosis. Emerging evidence suggests that failed resolution of inflammation and defective phagocytosis or efferocytosis underpins several prevalent human diseases. Therefore, understanding factors and mechanisms associated with enhancing these processes is a critical need. SPMs enhance phagocytosis and efferocytosis and this review will highlight mechanisms associated with their actions.